ESTUDO DA COMPATIBILIDADE ENTRE IRM E ITIL NA GESTÃO DE ATIVOS DE TI (PESQUISA DE CAMPO: TELEMAR) - Côrtes, Renato Augusto dos Santos (2005)
The present work intends to present a comparative evaluation among the IRM (Infrastructure Resource Management) methodology and the ITIL (IT Infrastructure Library) methodology in what concerns the control of assets of IT in computation environment in the companies. Based on the foundations of the IRM methodology for control of assets of IT a method was implemented for inventory of equipments of IT with the objective of optimizing the administration of these assets, allowing the administration and the software auditing. The research environment and implementation was a great company of the branch of Telecommunications, Telemar, with the implantation of methodology of IT assets control . The lifted up hypotheses were the following ones: (1) the implantation of the control of assets of IT in Telemar done according to the IRM methodology is compatible with the best practices of delivery of services in IT proposed by ITIL, (2) the implantation of the control of assets of IT in Telemar done according to the IRM methodology is compatible with the best support practices to services of IT proposed by ITIL, (3) the implantation of the control of assets of IT in Telemar done according to the IRM methodology allowed the company to be using IT to reach a better strategic positioning and sustainable competitive advantage. The hypotheses (1), (2) and (3) were tested through the comparison among the results reached in the implantation of the methodology and the foundations of the ITIL ethodology , considered to be a pattern today in administration of IT services.